Persepsi dan Partisipasi Masyarakat Lokal terhadap Pengembangan Kawasan Ekonomi Khusus Mandalika di Lombok Tengah - Irwan, Lalu Sandika; Widawati, Ida Ayu Putri; Wiarti, Luh Yusni (Tulisan Ilmiah Pariwisata (TULIP), 2022)
The Tourism sector has become one of the drivers of the regional economy, including in West Nusa Tenggara through the development of the Mandalika Special Economic Zone (SEZ) in Central Lombok. The development of this area provides new hope for the welfare of the local community. However, until the development process enters the final stage, there are still pros and cons from the lokal community regarding the development of the Mandalika SEZ. So far, there is no real picture of the perceptions of local communities and their forms of participation in response to these perceptions.This study aims to (1) explore and assess local community perceptions and (2) analyze local community participation in the development of the Mandalika SEZ in Central Lombok. Data were collected using a questionnaire methode, observation and indepth interview from local communities in the three supporting villages of the Mandalika SEZ which had been determined using purposive sampling. The collected data is then analyzed descriptively and interpreted based on literature review. The findings of this study indicate that the local community has a positive perception of the development of the Mandalika SEZ from the enverionmental, socio-culture, and economic aspects. Communities began to be involved and participate in the management of destination. The form of local community participation is classified as consultation within the scope of the Mandalika SEZ development stage, namely two-way communication is established, the local community begins to listen to their ideas and opinions, but the decision and control remains with the developer. Thus, it illustrates that the development of the Mandalika SEZ is currently in the involvement stage and the local community has build their independence in maintaining the conduciveness of the Mandalika SEZ.